Framing Media on the Polemic Omnibus Law in Urban Communities Indonesia - Ihsan Suri; Umar Halim; Arsenius Wisnu Aji Patria Perkasa (International Journal of Media and Communication Research (IJMCR), 2023)
The demonstration occurred because of a form of rejection of one thing done by policymakers in making a regulation that would be implemented as a whole. In addition, demonstrations are also one of the ways that have been arranged to convey g the aspirations that want to be conveyed to a problem. In addition, several articles in the Job Creation Law are being submitted to the Constitutional Court for Judicial Review because they are considered to have legal defects in their discussion, where several laws are considered too partial to state organizers. The public assesses the urgency, where the ratification of the Job Creation Law looks like a rush and a rush, so it lacks input from various parties. Recently, there have been large-scale demonstrations carried out in various regions in Indonesia related to the rejection of the ratification of the Job Creation Law, commonly called the Omnibus Law, or it can be said to be the Sapu Jagat Law. This is due to the large amount of speculation and information that develops in the community, causing a negative sentiment from the public toward the government. By using framing theory, the author found that this negative sentiment arises as a result of defects in public communication conveyed from the government as stakeholders and policymakers and regulations that will be applied to the community. In the end, this negative sentiment caused a very massive impact, namely the increasing national instability.